Expanding the envelope : flight research at NACA and NASA - Gorn, Michael H. (Lexington, Ky. : University Press of Kentucky, 2001)
"Flight research takes up where the other instruments of aeronautical research - wind tunnels, fluid dynamics, and mathematical analysis - leave off. No matter how the equations suggest an aircraft ought to fly, only by studying actual flight, often in demanding, complicated, and dangerous maneuvers, can researchers discover the limits of flight and the true characteristics of experimental flight vehicles. The National Advisory Committee for Aeronautics (1915) and its successors, The National Aeronautics and Space Administration (1958), led the world in these endeavors." "Expanding the Envelope is the first book to explore the full panorama of flight research history. Michael H. Gorn writes of the early experiments conducted by England's Sir George Cayley, who in the nineteenth century tested kites and gliders by subjecting them to experimental flight, and of the Wright brothers' work in the redesign and calibration of flight surfaces in order to achieve the greatest lift and control. He details the creation of NACA and the pivotal discoveries it made in the areas of pressure distribution, flying qualities, and transonic research and brings the story to the present cutting-edge aeronautical research conducted at NASA today." "Gorn also explores the vital human aspect of the history of flight research, including the contributions of such well-known figures as James H. Doolittle, Chuck Yeager, and A. Scott Crossfield, as well as the equally important engineers pilots and scientists who also had the "Right Stuff". While the individuals in the cockpit often receive the lion's share of the public's attention, Expanding the Envelope shows flight research to be a collaborative activity, one in which the pilot participates as part of an engineering team." "Here is more than a century of flight research, from well before the creation of NACA to its rapid transformation under NASA. The Book explores recent developments in commercial aviation and military aeronautics and gives a behind-the-scenes look at the development of groundbreaking vehicles, such as the X-1, the D-558, and the X-15, which demonstrated manned flight at speeds up to Mach 6.7 and as high as the edge of space."--Jacket
Something New in AerodynamicsA New Analytical Tool; A Page Turns; 8 New Directions; A Prophecy Fulfilled; The Salve of Important Work; An Old-Fashioned Program; An Independent Entity; Access to Space; New Responsibilities; Air and Space; Epilogue; Notes; Glossary; Index
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: United States. -- National Aeronautics and Space Administration; United States. -- National Advisory Committee for Aeronautics; United States. -- National Advisory Committee for Aeronautics; United States. -- National Aeronautics and Space Administration; Aeronautics -- Research -- United States; Aéronautique -- Recherche -- États-Unis.; TRANSPORTATION -- Aviation -- General; Aeronautics -- Research; United States